The growth-differential effects of domestic investment and foreign direct investment in Africa - Victor U. Ijirshar; Gbatsoron Anjande; Joseph Fefa; Bridget N. Mile (CBN Journal of Applied Statistics, 2019)
This paper employs dynamic panel models; Pooled Mean Group (PMG) and Mean Group (MG) estimators to assess the growth-differential effects of Foreign Direct Investment (FDI) and Domestic Investment (DI) among 41 selected African countries from 1970 to 2017. The result of Hausman test shows that PMG estimator is preferred. The study found that FDI and DI are important grease for growth of African countries in the long-run. The study also found that inflows of FDI crowds-in DI in Africa and that there is significant difference in the growth effects of foreign direct investment and domestic investment while the joint effects of foreign direct investment and domestic investment on growth of African countries is found to be statistically significant. In the short-run, estimates show that foreign direct investment has negative influence on growth of 24 countries out of which four (Benin, Madagascar, Nigeria and Equatorial Guinea) are highly significant at 5% level, while the estimated influence of domestic investment on growth of most African countries was positive. This shows that foreign direct investment in Africa has negative effects on growth of host economies in the short-run. The study recommends that African governments should continually encourage domestic savings and investment as major source of growth and only consider FDI as a growth supplement
Keywords: E62; F21; F43; O4; 330; African countries; economic growth; developing economies; domestic investment; foreign investment and foreign direct investment